2014
DOI: 10.1089/humc.2014.067
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Safety Evaluation of a Recombinant AAV8 Vector for X-Linked Retinoschisis After Intravitreal Administration in Rabbits

Abstract: X-linked retinoschisis (XLRS) is a retinal disease caused by mutations in the gene encoding the protein retinoschisin (RS1) and one of the most common causes of macular degeneration in young men. Currently, no FDA-approved treatments are available for XLRS and a replacement gene therapy could provide a promising strategy. We have developed a novel gene therapy approach for XLRS, based on the administration of AAV8-scRS/IRBPhRS, an adeno-associated viral vector coding the human RS1 protein, via the intravitreal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…Furthermore, the present study was not designed to differentiate whether the vg content-related responses were due to the mere presence of AAV genome or whether transcriptional and/or translational activities had a role in inflammation. Additional research will be necessary to address these intriguing questions; reports by Marangoni et al 12 and Maclachlan et al, 9 however, indicated minimal impact of gene expression on inflammation. Regardless, the data presented in this study suggest that enrichment for genome containing capsids improves retinal transduction and reduces VC inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the present study was not designed to differentiate whether the vg content-related responses were due to the mere presence of AAV genome or whether transcriptional and/or translational activities had a role in inflammation. Additional research will be necessary to address these intriguing questions; reports by Marangoni et al 12 and Maclachlan et al, 9 however, indicated minimal impact of gene expression on inflammation. Regardless, the data presented in this study suggest that enrichment for genome containing capsids improves retinal transduction and reduces VC inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Both SR and IVT ocular AAV vector dosings in higher species induce mild and temporary inflammatory responses, which are stronger when dose levels increase. [9][10][11][12] Foreign protein and foreign DNA are known inducers of inflammation, which is also true in the immune-privileged ocular environment. 13,14 We designed a series of studies to explore which component(s) of AAV vectors, viral capsid, or viral DNA drive inflammatory responses following IVT dosing of AAV vectors.…”
Section: Introductionmentioning
confidence: 99%
“…40 Similarly, Marangoni et al reported inflammatory cell infiltrates in the vitreous of New Zealand White rabbits after intravitreal delivery of AAV8 coding the human retinoschisin protein. 41 Despite these observations, a phase I/IIa clinical dose-escalation trial (NCT02317887) was conducted to evaluate the safety and efficacy of AAV8-RS1 in nine patients with molecularly confirmed RS1 Xlinked retinoschisis. 5 Cukras et al reported that the virus was well tolerated in all but one of the individuals, but they also observed dose-dependent inflammation, including an increase in systemic antibodies raised against the AAV8 capsid.…”
Section: Discussionmentioning
confidence: 99%
“…Some level of caution may be warranted in developing this approach, however, as there are reports of viral transduction extending outside the eye to sites including the optic nerve, brain, and other tissues after intravitreal injection, 54,55 and there is also a concern that inflammation may persist in the eye after higher viral doses. 56 The rare nature of most retinal dystrophies, coupled with the genotypic and phenotypic heterogeneity observed in patients, means that only a relatively small number of individuals might benefit from treatments targeting specific gene mutations. This raises issues relative to whether the costs of developing such therapies can be recovered after market authorization, and how to encourage investment in therapies for rare diseases that may involve only a single administration.…”
Section: Challenges and Potential Barriersmentioning
confidence: 99%